Mental Health Status and Literacy of Adolescent in Rural Area of Mojokerto, East Java, Indonesia - Ardana, Arin Aurilia; d'Arqom, Annette; Puteri, Fira Adilah; Indiastuti, Danti Nur; Nasution, Mhd Zamal; Qorib, Mohammad Fathul; Setiawati, Yuani; Junaidah Yusof; Hasanatuludhhiyah, Nurina (Jurnal Psikiatri Surabaya, 2025)
Introduction: Adolescence is a crucial period for the development of mental health. Enhancing mental health literacy can reduce stigma and support early intervention and treatment. This study aims to examine the mental health status and mental health literacy among middle and late adolescents in a rural area of Mojokerto District, East Java, Indonesia. Methods: A total of 81 high school students from Mojokerto District participated in the study. The Depression Anxiety Stress Scale – Youth version (DASS-Y) was used to assess symptoms of depression, anxiety, and stress. Mental health literacy was measured using the Adolescent Mental Health Literacy Questionnaire (AMHL). The validity of the AMHL was tested on 30 students using Pearson correlation. Descriptive statistics were used to analyze the prevalence of mental health conditions and levels of mental health literacy. Inferential statistics were applied to explore associations between mental health status, literacy, and sociodemographic variables. Results: The results showed that 53% of students experienced symptoms of mental health problems. While most students demonstrated moderate to satisfactory mental health literacy, significant gaps remain. Enhancing literacy may help reduce stigma and improve knowledge and attitudes toward mental health. Sociodemographic factors and mental health literacy showed limited influence on mental health status. However, sex was significantly associated with both mental health literacy and mental health status (p = 0.016 and p = 0.032, respectively). Conclusion: Mental health during adolescence significantly influences adult well-being. Improving adolescent mental health literacy is crucial for early recognition, stigma reduction, and better access to mental health care.